ANALISIS KESULITAN BELAJAR SISWA PADA MATERI TUMBUHAN KELAS X DI SMAN 1 RAMBAH HILIR TAHUN PEMBELAJARAN 2014/ 2015 - Marisa, Popi (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
This student was almed to determine analiysis difficulty student learning at plant class X of SMAN 1 Rambah Hilir for academic on years 2014/2015. The method of this study was descritive and purposive sampling techniques. Sample of this study is class of X-3 which amounting to 32 student . Result showed that score of difficulty student learning with an average of 70,85% which concluded in enough category. The higher indicator was found in parent of congeniality with an average 82,90% which concluded in enough category. The lower indicator was found in teacher method teaching with an average 59,37% which concluded in less category.